Endogean and cavernicolous Coleoptera of the Balkans. XXIV. Amauropini (Coleoptera: Staphylinidae: Pselaphinae) from the collection of the Moravian Museum in Brno - Hlaváč, Peter; Baňař, Petr; Koukalová, Kateřina (Zootaxa, 2021)
The status of Amauropus lobipes Reitter, 1918 and Protamaurops bicarinata (Reitter, 1918) is confirmed based on the holotypes housed at the Moravian Museum in Brno, Czech Republic. Both species are redescribed, photographed, and the aedeagus of Amauropus lobipes is illustrated. A checklist of Amauropini species in the Moravian Museum is given.